PKM Edukasi Kejadian Demam Berdarah Dengue Terhadap Dampak Yang Di Timbulkan Hujan Di Kelurahan Buntusu Makassar - Hilal, Achmad; Yusnayanti, Cici; Mildaratu, Mildaratu; Putri, Safridha Kemala; Nasution, Titi Anggraini; Fitriyanstanti, Devi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Abiotic factors such as rainfall, temperature and evaporation can influence the failure of mosquito eggs, larvae and pupae to become adults. Dengue hemorrhagic fever is still a public health problem and the incidence of cases fluctuates erratically. One of the causes of Dengue Hemorrhagic Fever is rainfall. Dengue prevention and control relies on effective vector control measures. Dengue prevention and control strategies require community involvement. Therefore, it is important to provide health education to the public regarding the prevention of Dengue Hemorrhagic Fever by promoting the 3M Plus Mosquito Nest Eradication Program. The method used is education which aims to increase the knowledge of the Indonesian people regarding the prevention and management of Dengue Hemorrhagic Fever. Based on the geographical location and topography, the Bunsusu district of Makassar has hot temperatures. In the rainy season, the incidence of dengue hemorrhagic fever cases usually tends to increase, where the highest rainfall occurs in February to April, while the lowest is in August and September. This type of research is analytical observational research with multi temporal analysis. The data used in this research is secondary data on cases of dengue hemorrhagic fever, data on rainfall factors. The distribution of dengue hemorrhagic fever cases is clustered in residential areas. The power of rainfall with dengue hemorrhagic fever is strong. There is no significant correlation between rainfall factors and dengue hemorrhagic fever. This may be caused by the lack of duration of the data taken, the incomplete physical factor data obtained and the influence of other more dominant factors.